Eliciting women's preference for prenatal testing in China: a discrete choice experiment - Liangzhi Wu; Yanxin Wu; Shiqian Zou; Cong Sun; Junyu Chen; Xueyan Li; Zihang Lin; Lizhi Guan; Qing Zeng; Sihan Zhao; Jingtong Liang; Rui Chen; et al. (BMC, 2020)
Abstract Background Pregnancy tests can be used for the early diagnosis of fetal problems and can prevent abnormal birth in pregnancies. Yet, testing preferences among Chinese women are poorly investigated. Methods We developed a Discrete Choice Experiment with 5 attributes: test procedure, detection rate, miscarriage rate, time to wait for result, and test cost. By studying the choices that the women make in the hypothetical scenarios and comparing the attributes and levels, we can analyze the women's preference of prenatal testing in China. Results Ninety-two women completed the study. Respondents considered the test procedure as the most important attribute, followed by detection rate, miscarriage rate, wait time for result, and test cost, respectively. The estimated preference weight for the non-invasive procedure was 0.928 (P < 0.0001). All other attributes being equal, the odds of choosing a non-invasive testing procedure over an invasive one was 2.53 (95% confidence interval, 2.42-2.64; P < 0.001). Participants were willing to pay up to RMB$28,810 (approximately US$4610) for a non-invasive test, RMB$6061(US$970) to reduce the miscarriage rate by 1% and up to RMB$3356 (US$537) to increase the detection rate by 1%. Compared to other DCE (Discrete Choice Experiment) studies regarding Down's syndrome screening, women in our study place relatively less emphasis on test safety. Conclusions The present study has shown that Chinese women place more emphasis on detection rate than test safety. Chinese women place great preference on noninvasive prenatal testing, which indicate a popular need of incorporating noninvasive prenatal testing into the health insurance coverage in China. This study provided valuable evidence for the decision makers in the Chinese government.